The ars poetria in Films: Repercussions of Geoffrey of Vinsauf´s Theory of Amplification in Audiovisual Narrative - Juan Manuel Arriaga Benítez (Medievalia)
In this work it has been analized the participation of figures or techniques of amplification described by Geoffrey of Vinsauf, norman poet from 13th century, into the classical rhetoric dimensions known as dispositio (structure) and elocutio (style), so that I can exemplify how in film industry it can be witnessed its use in form of image design through cinematography, visual composition and scenic assembly. From this study, it is also possible to notice how screenwriters and directors have been able to offer moral or emotional meaning to the viewer.